Asuhan Keperawatan Jiwa Pada Tn. K Dengan Masalah Utama Risiko Perilaku Kekerasan Akibat Skizofrenia Tak Terinci Di Ruang Gatotkaca RSJD dr. Amino Gondohutomo Provinsi Jawa Tengah - Aulia Nur Hasanah; Slamet Wijaya (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Background: Schizophrenia is a serious chronic mental disorder that can affect thinking, perception, feelings, and behavior. Patients with undifferentiated schizophrenia are at risk of experiencing the nursing problem of risk of violent behavior (RPK) due to their inability to control emotions and anger. Based on data from the medical records of RSJD dr. Amino Gondohutomo, Central Java Province, from August to October 2025, the risk of violent behavior was the highest nursing diagnosis in the Gatotkaca Ward, reaching 56.5%–77% of all inpatients. Objective: To perform nursing care on Tn. K with the main problem of risk of violent behavior due to undifferentiated schizophrenia at RSJD dr. Amino Gondohutomo, Central Java Province. Methods: This study used a descriptive method with a nursing process approach. Data collection was carried out through interviews, observation, documentation studies, and literature review. Nursing care was provided from November 18 to 22, 2025. Results: Assessment findings on Tn. K (19 years old) with undifferentiated schizophrenia and a history of physical abuse, parental rejection, and family violence revealed four nursing problems: risk of violent behavior (core problem), sensory perceptual disorder: auditory and visual hallucinations, self-concept disorder: low self-esteem, and self-care deficit. Implementation was carried out through nursing strategies (SP) 1 to 4 for risk of violent behavior (physical, medication, verbal, and spiritual control), SP 1 and SP 3 for self-care deficit, and SP 1 to SP 2 for sensory perceptual disorder: hallucinations. All implementation stages were optimally achieved. Conclusion: Nursing evaluation showed that the client was able to achieve cognitive, affective, and psychomotor goals in all implemented SPs. Collaboration with ward nurses was carried out to continue SP 3 and SP 4 for hallucinations and the entire low self-esteem intervention due to time constraints.